Information and Communication Technology for Well-Informed Farmers in Pakistan: Current Status and Immediate Proposed Solution: ICT for Well-Informed Farmers in Pakistan - Minhas, Sidra; Sabahat, Nosheen (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Owing to geographical location, agriculture is a vital sector for Pakistan’s economy. Agriculture contributes 18.9% to the Gross Domestic Product of Pakistan therefore constant augmentation of this sector needs attention. Over the past decade, no major growth in the agriculture sector has been observed and a recent notable decline in crops has raised several concerns. Apart from natural disasters, a major reason behind this drop is outdated farming practices. Majority of the farms are cultivated and harvested using decades old techniques involving huge manpower and very low mechanization or technology. In this paper, current practices adopted in various farming stages in Pakistan were discussed. Alongside, the status of Information and Communication Technology (ICT) interventions in those stages is described. Reasons behind abstinence of technology into various phases of farming were also enlisted. After detailed description and analysis of the issue, guidelines to an ICT related solution which will be easily accepted by local and small-scale farmers was proposed.